Use of Gadgets by Early Childhood in the Digital Age to Increase Learning Interest - Dhenni Vicky; Held Adrianna; Breit Phan (Scientechno: Journal of Science and Technology, 2023)
In the millennial era, most human needs are digitalized and can be arranged using gadgets. The use of devices is now spreading worldwide, so it is a challenge for parents and PAUD and SD educators to face the era of the industrial revolution 5.0. In Indonesia, the use of gadgets has many negative impacts, especially in early childhood at this time. This phenomenon is the background of the current problem. In the current era, a descriptive qualitative method was created, and it aims to find out the use of gadgets that can support early childhood learning media modes. The data collection process was carried out through observation of early childhood aged 4-6 years, some of whom were already proficient in using gadgets, interviews with parents who gave devices to early childhood, and documentation related to children using devices in the learning process to looking for various kinds of learning that can be drawn from the benefits of using these gadgets and children are freer to use widgets to find important tasks. From the research results, the use of devices can increase interest in early childhood learning in the learning process. So that for early childhood it can be beneficial as a tool to complete processing facilities for early childhood.